2022
DOI: 10.21203/rs.3.rs-2083365/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A comparison of machine learning models’ accuracy in predicting lower-limb joints’ kinematics, kinetics, and muscle forces from wearable sensors

Abstract: Gait analysis outside the laboratory has been possible by recent advancements in wearable sensors like inertial measurement units (IMUs) and Electromypgraphy (EMG) sensors. The aim of this study was to compare performance of four different non-linear regression machine learning (ML) models to estimate lower-limb joints’ kinematics, kinetics, and muscle forces using IMUs and EMGs’ data. Seventeen healthy volunteers (9F, 28 ± 5 yrs) were asked to walk over-ground for a minimum of 16 trials. For each trial, marke… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 54 publications
0
0
0
Order By: Relevance
“…The RMSE values for joint kinematics stayed well below the 5° error threshold, which is often considered a clinically acceptable level of deviation for assessing joint movements(Slater et al, 2018). However, the joint kinematics exhibited a slight increase compared to personalized models developed for adults in other studies, where observed values ranged from 1.38° to 3.96° for all targets(Moghadam et al, 2023a, Yeung et al, 2023, Findlow et al, 2008, Giarmatzis et al, 2020.…”
mentioning
confidence: 78%
See 3 more Smart Citations
“…The RMSE values for joint kinematics stayed well below the 5° error threshold, which is often considered a clinically acceptable level of deviation for assessing joint movements(Slater et al, 2018). However, the joint kinematics exhibited a slight increase compared to personalized models developed for adults in other studies, where observed values ranged from 1.38° to 3.96° for all targets(Moghadam et al, 2023a, Yeung et al, 2023, Findlow et al, 2008, Giarmatzis et al, 2020.…”
mentioning
confidence: 78%
“…2, Step 5). The hyperparameters for both RF and CNN models were chosen based on previously optimized models (Moghadam et al, 2023a). We employed an RF model comprising 500 trees, each with a maximum depth of 25.…”
Section: Non-linear Regression ML Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Endzhievskaya et al [31] suggested a preference for using the RF model in machine learning due to its ease of use and minimum number of hyperparameters for tuning. Compared to machine learning models such as DT, CNN, and LSTM, the RF model has demonstrated higher predictive accuracy in certain application scenarios [32][33][34]. The aforementioned studies indicate that the RF model may offer better predictive performance in data prediction.…”
Section: Introductionmentioning
confidence: 99%